Specialization and Injury Risk in Different Youth Sports: A Bio-Emotional Social Approach - Iona, Teresa; Raimo, Simona; Coco, Daniele; Tortella, Patrizia; Masala, Daniele; Ammendolia, Antonio; Mannocci, Alice; La Torre, Giuseppe (Frontiers in Psychology, 2022)
Aim: Sport specialization is an actualu trend in youth athletes, but it can increase injury risk. The aim was to determine the eventual correlation between sports specialization and injury risk in various sports, using a biopsychosocial approach. Methods: 169 sport-specialized athletes completed [(38 female, 131 male); (11,2 ± 2,7 yrs); (56.28 ± 15.72 kg);(161.3 ± 15.52cm)] a self-reported questionnaire regarding sociodemographic (age, gender, educational level), physical-attitudinal, injuries and psychological-attitudinal To analyze data univariate and correlate analyses were used. Results: Of 169 athletes enrolled, 53% were single-sport specialized (reported participation in one sport and trained >8 months/year). In team sports (100%, OR = 0,75; p = ,022) a high risk of having to remain at rest for up to 1 month because of overuse was observed. Males who suffered direct trauma (70%; OR = 1,03; p = ,006) in the team group (95%, OR = 0,09; p = ,008) were more exposed to that type of injury, and also the type of specialization figured significantly (p = ,047). In addition, interoceptive awareness correlates with injury (95% ,1.04, p=0.01). Conclusions: Athletes in team sports are more specialized, a higher training volumes, greater rates of injuries correlated with interoceptive awareness than in individual sports.